PENGARUH UKURAN DEWAN PENGAWASAN SYARIAH, UKURAN DEWAN KOMISARIS, KOMITE AUDIT, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING: STUDI EMPIRIS PADA BANK UMUM SYARIAH DI INDONESIA PADA TAHUN 2014-2018 - Putri Meliya Annisa; Sari Nelly Ria; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Islamic Social Reporting (ISR) is an index of social responsibility disclosure whose indicators are specific to Islamic ethical principles. In this study, an assessment of the level of ISR disclosure was carried out on companies that were included in Islamic Commercial Banks in Indonesia during the 2014-2018 period. This study aims to obtain empirical evidence regarding the analysis of the factors that affect the disclosure of Islamic Social Reporting (ISR). The factors used include the size of the Sharia supervisory board, board of commissioners, audit committee, and company age. The measurement of Islamic Social Reporting (ISR) is based on the Islamic Social Reporting category to measure the ISR index as seen from the Bank's annual report. This research is a quantitative research. The population in this study were all Islamic commercial banks in Indonesia, amounting to 14 units of Islamic commercial banks based on data from the Financial Services Authority (OJK). The sampling technique used was purposive sampling. The total sample is 12 Islamic commercial banks. Data analysis was performed by using classical assumption tests and hypothesis testing using multiple regression methods. The results of this study indicate that the size factor of the Sharia supervisory board has no significant effect on the disclosure of Islamic Social Reporting. The board size factor has a significant effect on the disclosure of Islamic Social Reporting. The audit committee factor has no effect on the disclosure of Islamic Social Reporting and company age has a significant effect on the disclosure of Islamic Social Reporting.Keywords: Islamic Social Reporting (ISR) Disclosure, Sharia Supervisory Board Size, Board of Commissioners, Audit Committee and Company Age.